Penyidikan Tindak Pidana di Bidang Ketenagakerjaan oleh Penyidik Pegawai Negeri Sipil (PPNS) Dinas Tenaga Kerja dan Transmigrasi Provinsi Sumatera Barat - Gemilang, Zaifi Surya; Zurnetti, Aria; Khairani, Khairani (UNES Law Review, 2023)
Criminal activities in the labor industry are illegal acts carried out by laborers, employers, or other persons not affiliated with the firm that face criminal penalties under the Criminal Code, Manpower Law, and/or other legislation, either alone or in combination. In the course of Civil Servant Investigators' criminal inquiries in the labor sector. The Manpower and Transmigration Service (Disnakertrans) employs Civil Servant Investigators who carry out their work in accordance with the Law Number 13 of 2003 concerning Manpower and the Regulation of the Chief of the National Police of the Republic of Indonesia Number 6 of 2010 concerning Investigation Management by Civil Servant Investigators (PPNS). Both laws provide authority for their operations. It seems sense in this instance that PPNS Disnakertrans's inquiry is coordinated with the police as well. One of the issues preventing the inquiry from operating at its best in its execution is the ineffective coordination. The following issues may be created based on the backdrop of the aforementioned difficulties: 1. How are criminal investigations in the area of labor being carried out by Civil Servant Investigators (PPNS) of the Manpower and Transmigration Office of West Sumatra Province? 2. What are the challenges facing the Civil Servant Investigators (PPNS) of the Manpower and Transmigration Office of the Province of West Sumatra in carrying out criminal investigations in the area of labor? Based on the study's descriptive methodology and empirical juridical approach, the following conclusions may be drawn from it: 1. The implementation of criminal investigations in the field of labor by PPNS Disnakertrans is a series of: examination, processing of crime scenes, Sprindik, SPDP, examination of witnesses and suspects, completion and submission of Case Files to be submitted by PPNS to the public prosecutor through police investigators. 2. The obstacles experienced by PPNS Disnakertrans in carrying out criminal investigations in the field of labor are the lack of supervisors and PPNS both in quantity and quality. In addition, the lack of facilities and infrastructure as well as limited budget are obstacles in the investigation. SOPs that are not fully implemented and lack of coordination between PPNS and the Police as Korwas are obstacles found in the implementation of criminal investigations in the field of labor. For better implementation of investigations, PPNS Disnakertrans West Sumatra must be able to improve coordination with Police Investigators. In addition, Disnakertrans is expected to be able to overcome internal obstacles so that the enforcement of criminal acts in the labor sector can run even better.